Assistance in Writing Scientific Articles for Students Through a Workshop-Mentoring-Peer Review Model - Niswatin Nurul Hidayati (TAAWUN, 2025)
This scientific article writing assistance program aims to improve academic literacy and foster scientific writing skills among KMI Assalam students. The implementation method consists of three stages: preparation, implementation, and evaluation. In the initial stage, needs analysis and personal learning plan design are carried out. The implementation phase includes training in research methodology, academic writing techniques, and individual feedback sessions and peer review. Evaluation was carried out by assessing the student's final manuscript, reflective journals, satisfaction surveys, and focus group discussions. The results of the program showed a significant increase in students' ability to write scientific articles, both in terms of writing structure, the use of academic references, and confidence in conveying ideas scientifically. This activity also forms a collaborative and reflective scientific culture in the school environment. This program makes a positive contribution to strengthening students' academic capacity and becomes an effective model in building a sustainable scientific literacy ecosystem at the senior high school.